Analisis Framing Analisis Framing Pemberitaan Grup Fantasi Sedarah Pada Media Detik.Com Dan Kompas.Com: Analisis Framing Pemberitaan Grup Fantasi Sedarah Pada Media Detik.Com Dan Kompas.Com - yuniar, farrah; Yusup, Eka; Sianturi, Hendri Roris P. (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
This study aims to understand how the news framing of the 'Grup Fantasi Sedarah' case is carried out by two national online media outlets, Detik.com and Kompas.com. The research uses a qualitative descriptive method with Robert N. Entman’s framing analysis model. The study focuses on four framing elements: Define Problems, Diagnose Causes, Make Moral Judgement, and Treatment Recommendation. The results show that Detik.com emphasizes problem definition and solutions using straightforward language, while Kompas.com focuses more on causes and moral evaluations with a more analytical and cautious writing style. Both media exhibit different ideological tendencies in constructing moral deviation issues in the digital sphere. These findings illustrate how media shape public perception through the way news is presented.